Media Role in Democracy and Human Rights: Challenges to Civil Society Life in Indonesia - jerry indrawan (PRoMEDIA, 2015)
Since the reformation era, where democracy has been fully practiced, Indonesia entered a new and more tolerant era. It characterized by high appreciation of human rights and democratic way of living. However, human rights stand on various assumptions that really fragile, for example, the freedom of speech enables us to talk about problems that are very sensitive to some people or culture. This is where media take part. In an era of information, media plays a big role in terms of human rights promotion and upholding democracy. Media role in the era of information technology has developed rapidly, especially in democratic environment. Media not just play as an information carrier, but had also transform themselves as the center of information itself. As a part of the civil society, media enable every layer of the society to access information freely and openly. Such condition will bring different understanding from each communicant. Media as communicator, distorted the essence of information that leads to misinterpretation. If a communal society unable to clearly digested or misunderstand information, conflicts will be potentially arise among them. Poverty, ethnic diversity, repressive political system, and fight for resources are conventional sources of conflict, but media is a modern means to create conflicts at all level of society, and various sources also. Media provide their journalistic products in much more businesslike and straight-out. Social reality is generated and constructed outside formal authority. In this case, media is able to influence public opinion by doing framing analysis to a news. Framing analysis is an approach to find out the perspective use by reporters in selecting issues and write stories. The perspective eventually determined which facts are taken, which parts are shown or omitted, and also the purpose of where the story leads. This is certainly a threat to democracy and human rights, because it can generates conflicts. Keywords: Media, Democracy, Human Rights, and Civil Society